Design the key concepts - McDermott, Catherine (Routledge, 2007)
This is the essential student's guide to Design – its practice, its theory and its history. Drawing from a wide range of international examples, respected design writer Catherine McDermott explores key topics including: international design – from Europe to Africa design history – from Art Nouveau to punk sustainable design, recycling and green design design theory – from semiotics to gender, to postcolonialism design technology, graphic design and the web. Fully cross-referenced, with up-to-date guides for further reading, Design: The Key Concepts is an indispensable reference for students of design, design history, fashion, art and visual culture.